Respostas

A melhor resposta!
2013-06-24T16:47:25-03:00

a=2

b=-3

c= -20

 

delta= 9 - 4 x 2 x -20

delta= 9 + 160

delta= 169

 

x¹= 3 + raiz quadrada de 169 / 2xa

x¹= 3 + 13 / 2 x 2

x¹ = 16/4

x¹ = 4

 

 

x²= 3 - raiz quadrada de 169 / 2 x a

x²= 3 -13 / 2 x 2

x²= -10 /4 (simplifica por 2)

x² = -5/2 ou em número decimal -2,5

 

1 5 1
2013-06-24T17:24:06-03:00

2y²-3y-20=0

 

a=2; b=-3; c= -20

 

Delta= b² - 4.a.c

Delta= (9) - 4 x 2 x -20

Delta= 9 + 160

Delta= 169 

Delta= \sqrt{169}

 

x= -b +/- \sqrt{Delta} / 2.a

x= -(-3) +/- \sqrt{169} / 2.2

x= 3 +/- 13 / 4

 

x¹= 3 + 13 / 4

x¹ = 16/4

x¹ = 4

 

x²= 3 -13 / 4

x²= -10 /4 (podemos simplificar por 2)

x² = -5/2